The Analysis Of Student And Lecturer Responds Of Online Learning During Covid-19 Pandemic - Halisah Suriani; Isnaini I (EDUCATION JOURNAL OF INDONESIA, 2020)
This research was conducted from Monday to Wednesday, July 6 to 8, 2020 at the Biology Education Study Program, FKIP Gunung Leuser University, Kutacane, Southeast Aceh. The method used is an exploratory case study consisted of 5 people consisting of 2 Lecturers of Biology Education Study Program and 3 students who were selected using purposive sampling method. Data analysis uses thematic data. It can be concluded that online learning at the Biology education study Program, FKIP university, Gunung Leuser Kutacane is still not effectively implemented because lecturers and students have not optimally prepared themselves in the online learning process. Online learning is constrained by several things, including a weak intermet network, quotas and the availability of electronic devices, the incompatibility of the implementation of lectures with the schedule set by the study program and the aspect of giving less objective scores.